Desenvolvimento do sistema computacional CARTOMORPH para processamento de imagens de sensoriamento remoto - Cardim, Guilherme Pina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays, the increasing importance of the Geographic Information Systems and the necessity of acquisition and update of spatial data motivate researches about cartographic features extraction. In the urban planning field, the spatial data are used to planning and decision-making. Therefore, it is essential that these data are updated and accurate. Thus, to detect cartographic features using remote sensing images is a significant possibility, reason that these studies are of fundamental importance. Nevertheless, the content of the images involved complicates this procedure and makes it a challenging topic. Moreover, the software used for research about cartographic features extraction methodologies are, usually, of private domain and consequently have the functionalities blocked, disallowing changings and improvement of the algorithms. This sense, this work consists of a software development, named as CARTOMORPH, to remote sensing image processing. The software purpose is to allow the use of the functions implemented, as well as allow changings, adaptions and improving of the functions, since it is of public domain. So techniques of digital image processing, focused on the mathematical morphology theory, was implemented to enable the development of cartographic features extraction routines. The CARTOMORPH development is of fundamental importance, since it is focused on cartographic studies to detect interest features from remote sensing images...

Atualmente, pesquisas sobre extração de feições cartográficas de interesse são motivadas, sobretudo, pela crescente importância dos Sistemas de Informações Geográficas e a necessidade de aquisição e atualização de dados espaciais. No campo de planejamento urbano os dados espaciais são utilizados para planejamentos e tomadas de decisão. Para tanto, é imprescindível que estes dados sejam atuais e acurados. Deste modo, uma possibilidade é efetuar a detecção e/ou extração das feições de interesse a partir de imagens de sensoriamento remoto, motivo pelo qual tais estudos são de fundamental importância. Todavia, o que dificulta este procedimento é o conteúdo das imagens envolvidas, o que torna a extração de feições de interesse um tópico desafiador. Além disso, normalmente os sistemas computacionais utilizados para realizar estudos de extração de feições cartográficas são sistemas de domínio particular, tendo suas funcionalidades fechadas, impossibilitando o estudo, alterações e melhorias nesses algoritmos. Neste sentido, este trabalho consiste no desenvolvimento de um sistema computacional, denominado CARTOMORPH, para o processamento de imagens de sensoriamento remoto. Este sistema, implementado de forma livre e de domínio público, tem como finalidade possibilitar a utilização das funções implementadas, focadas no estudo de extração de feições por morfologia matemática...
Keywords: Cartografia; Processamento de imagens - Tecnicas digitais; Morfologia matemática; Sensoriamento remoto; Sistemas de informação geografica; Cartography